lo g 2 ( ( 1 + tan 1 ° ) ( 1 + tan 2 ° ) ( 1 + tan 3 ° ) . . . ( 1 + tan 4 5 ° ) ) = ?
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
The trigonometric identity, that if A+B=45, then (1+tanA) (1+tanB)=2 can help here.
We can rearrange the interior part as follows to use the identity: (1+tan1) (1+tan44) (1+tan2) (1+tan43) ... (1+tan45)
We can thus form 22 pairs of this, as there are 44 terms which can be paired to use the identity leaving (1+tan45).
Thus, the equation will be simplified as 2 x 2 x 2 x 2 x 2 ...2 x (1+tan45) Here 2 gets multiplied to itself 22 times, as there are 22 pairs
The value of tan 45=1 and substituting this value in the equation and writing the continued 2's exponent form, we get,
2 2 2 x (1+1)
2 2 2 x 2
Simplifying further using the law of exponents,
2 2 3
Now bringing the logarithm part back,
lo g 2 2 2 3
Let the product inside the parentheses of logarithm function be P P = ( 1 + tan 1 ° ) ( 1 + tan 2 ° ) . . . ( 1 + tan 4 5 ° ) = ( 1 + tan 0 ° ) ( 1 + tan 1 ° ) ( 1 + tan 2 ° ) . . . ( 1 + tan 4 5 ° ) P = ( 1 + tan 0 ° ) ( 1 + tan 4 5 ° ) × ( 1 + tan 1 ° ) ( 1 + tan 4 4 ° ) . . . ∵ tan 0 ° = 0 ⇒ ( 1 + tan 0 ° ) = 1 ⇒ ( 1 + tan 0 ° ) ( 1 + tan 1 ° ) ( 1 + tan 2 ° ) . . . ( 1 + tan 4 5 ° ) = 1 × ( 1 + tan 1 ° ) ( 1 + tan 2 ° ) . . . ( 1 + tan 4 5 ° ) = P Now using a identity (proved below) ; ( 1 + tan ( 4 5 ° − x ) ) ( 1 + tan x ) = 2
tan ( 4 5 ° − x ) + 1 = 1 + tan x 1 − tan x + 1 = 1 + tan x 1 − tan x + 1 + tan x = 1 + tan x 2 ⇒ tan ( 4 5 ° − x ) + 1 = 1 + tan x 2 Multiplying both sides by 1 + tan x ( 1 + tan ( 4 5 ° − x ) ) ( 1 + tan x ) = 2
⇒ P = 2 × 2 × 2 . . . × 2 = 2 2 4 6 = 2 2 3 ⇒ lo g 2 P = 2 3
Problem Loading...
Note Loading...
Set Loading...
Consider the product:
P = ( 1 + tan 1 ∘ ) ( 1 + tan 2 ∘ ) ( 1 + tan 3 ∘ ) ⋯ ( 1 + tan 4 5 ∘ ) = ( 1 + cos 1 ∘ sin 1 ∘ ) ( 1 + cos 2 ∘ sin 2 ∘ ) ( 1 + cos 3 ∘ sin 3 ∘ ) ⋯ ( 1 + cos 4 5 ∘ sin 4 5 ∘ ) = ( cos 1 ∘ cos 1 ∘ + sin 1 ∘ ) ( cos 2 ∘ cos 2 ∘ + sin 2 ∘ ) ( cos 3 ∘ cos 3 ∘ + sin 3 ∘ ) ⋯ ( cos 4 5 ∘ cos 4 5 ∘ + sin 4 5 ∘ ) = cos 1 ∘ 2 cos 4 4 ∘ ⋅ cos 2 ∘ 2 cos 4 3 ∘ ⋅ cos 3 ∘ 2 cos 4 2 ∘ ⋯ cos 4 4 ∘ 2 cos 1 ∘ ⋅ cos 4 5 ∘ 2 cos 0 ∘ = cos 4 5 ∘ ( 2 ) 4 5 = 2 2 3
Therefore lo g 2 P = 2 3 .